Peponocephala electra ... - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
29. Melon-headed Whale Peponocephala electra French: Péponocéphale / German: Breitschnabeldelfin / Spanish: Delfin de cabeza de melon Other common names: Electra Dolphin, Little Killer Whale, Many-toothed Blackfish Taxonomy. Lagenorhynchus electra Gray, 1846, type locality unknown. This species is monotypic. Distribution. Worldwide in tropical and subtropical waters from c.40° N to ¢.35° §, including the Gulf of Mexico, Arabian Sea, Bay of Bengal, South China Sea, and Timor Sea. Descriptive notes. Total length up to 280 cm; weight up to 275 kg. Neonates may be up to 100 cm long and weigh 15-20 kg. Male Melon-headed Whales tend to be slightly larger than females. The Melon-headed Whale is very similar in appearance to the Pygmy Killer Whale (Feresa attenuata). It is moderately robust in stature, with bulbous, although not overly round, head with barely visible beak, tall falcate dorsal fin, and sickle-shaped flippers. More triangularshaped head and more sharply pointed flippers distinguish it from the Pygmy ... : Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Delphinidae, pp. 410-526 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on pages 519-520, DOI: 10.5281/zenodo.6610922 ...